STUDY ON THE MASTICATION MOVEMENTS OF THE TEMPOROMANDIBULAR JOINT - Marinela CIORTAN; Liliana LUCA; Ruxandra LUCA (Fiabilitate şi Durabilitate)
This paper presents the results of a study on the temporomandibular joint biomechanics. The study aimed to determine the trajectories described by the mandible during the three types of movements: opening-closing, abduction-adduction and lateral movement. The results obtained can be used to determine biological mechanisms that can be used in the construction of robots, prostheses for the temporomandibular joint, etc.